2009
DOI: 10.2147/ce.s6002
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in multiple myeloma: an evidence-based review of its role in therapy

Abstract: Introduction: Multiple myeloma (MM) is a relatively common and incurable hematological malignancy. Currently, there is no single standard therapy, with choice of treatment dependent on individual patient factors. Lenalidomide is an immunomodulatory drug with potent antitumor, antiangiogenic, immunomodulatory, and proapoptotic activity in MM. Aims: To evaluate the evidence for the use of lenalidomide in its current indication in relapsed or refractory MM, and additionally its investigational use for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 126 publications
1
24
0
Order By: Relevance
“…In line with our observations, a previous study found that perifosine (2 μM) tended to reduce the clonogenic activity of normal CD34 + cells [31]. The immunomodulatory substance lenalidomide is highly effective in the treatment of multiple myeloma and MDS, but an important side effect is hematotoxicity [13,[20][21][22][23]. If combined with dexamethasone as initial multiple myeloma therapy, it increases thrombocytopenia and neutropenia significantly, but anemia only slightly, in comparison to dexamethasone alone [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our observations, a previous study found that perifosine (2 μM) tended to reduce the clonogenic activity of normal CD34 + cells [31]. The immunomodulatory substance lenalidomide is highly effective in the treatment of multiple myeloma and MDS, but an important side effect is hematotoxicity [13,[20][21][22][23]. If combined with dexamethasone as initial multiple myeloma therapy, it increases thrombocytopenia and neutropenia significantly, but anemia only slightly, in comparison to dexamethasone alone [32].…”
Section: Discussionsupporting
confidence: 90%
“…The immunomodulatory substance lenalidomide showed promising results in the treatment of different hematological malignancies such as multiple myeloma, myelodysplastic syndrome (MDS) and chronic lymphocytic leukemia (CLL) [13][14][15]. Immunomodulation, antiangiogenic effects and direct induction of cytotoxicity may contribute to the clinically documented efficacy of this agent [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This has begun to be addressed recently through studying the pharmacological properties of analogs or breakdown products of the drug experimentally and clinically (Richardson et al. ; Mahony et al. ; Beedie et al.…”
Section: Introductionmentioning
confidence: 99%
“…Further understanding of the molecular and morphological action of this drug will aid in uncovering newer, safer alternatives. This has begun to be addressed recently through studying the pharmacological properties of analogs or breakdown products of the drug experimentally and clinically (Richardson et al 2010;Mahony et al 2013;Beedie et al 2015Beedie et al , 2016. Our previous studies of an anti-angiogenic thalidomide analog, CPS49, demonstrated the drug leads to widespread loss of blood vessels throughout the limb, when applied at the time of rapid limb growth [Hamburger and Hamilton (HH) St 17-19 in the chicken embryo], and disrupts the actin cytoskeleton of endothelial cells in vitro (Therapontos et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…After full text screening, fifty-two publications were included: two practice guidelines 4,5 ; three systematic reviews [6][7][8] ; ten unique primary studies, of which five were full-text publications 1,2,9-11 and five were conference abstracts [12][13][14][15][16] . Forty-two publications were ancillary to the ten unique primary studies, including secondary analyses or follow-up data from the main publications (Table i).…”
Section: Literature Search Resultsmentioning
confidence: 99%